Treatment With Melatonin After Corneal Graft Attenuates Rejection - Zhu, Ziqian; Peng, Ruiping; Shen, Hongyi; Zhong, Lei; Song, Siqi; Wang, Tao; Ling, Shiqi (Frontiers in Pharmacology, 2021)
Background: Immunologic graft rejection is the main complication of corneal transplants. This study aimed to investigate the effect of melatonin (MT) on the rejection of corneal transplantation. Methods: Corneal allografts were performed by grafting corneas from BALB/ C mice to C57BL/6 hosts. MT (50 mg/kg) was intraperitoneally injected into the hosts every day from the day of transplantation. The survival of grafts was observed by slit lamp biomicroscopy, and inflammatory cell infiltration was detected by hematoxylin and eosin staining and immunohistochemistry. The balance of Teff and Treg immune cells in draining lymph nodes (DLNs) was detected by flow cytometry. The levels of cytokines related to the grafts and DLNs were detected using real-time fluorescence quantitative PCR. Additionally, we used the mouse macrophage line RAW264.7 to study the effect of MT on the activation of NLRP3 inflammatory body. Results: MT treatment improved the graft survival rate, reduced inflammatory cell infiltration in the graft, decreased the percentage of Th1/Th17 cells in the DLN, and increased the percentage of Treg cells. Melatonin inhibited the activation of the NLRP3 inflammasome, thereby reducing the expression of IL-1β and other related proinflammatory cytokines such as MCP-1, MIP-1, NLRP3, ASC, TNF-a and VEGF-A. (all p <0.05). Conclusion: Our study demonstrates that MT promotes the survival of mouse corneal grafts by inhibiting NLRP3-mediated immune regulation, reducing immune cell activation and cell migration, and inhibiting the production of inflammatory-related cytokines. Treatment with MT might provide a potential clinical therapeutic target for corneal transplantation.